PEMAKNAAN PEREMPUAN ANTARGENERASI TERHADAP PERKAWINAN - Miratus Sholekhah, Ana; Manalu, S. Rouli; Suryanto Gono, Joyo Nur (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2024)
The phenomenon of generational transition has given rise to a shift in perception and marriage patterns among women as a group that is culturally attached to this issue. This study aims to examine the meaning of marriage experienced by women across generations. Meaning emerges along with human efforts to develop themselves and their minds in social life as the Symbolic Interaction Theory used in this study. Through interviews with six respondents from two different generations, namely the Old Generation with a birth range of 1947-1980 and the Young Generation born around 1981 to the present and have reached the legal age for marriage, this study reveals that the shift in meaning occurs as a product of their experiences in socializing and consuming different information. The interpretative paradigm applied in the interpretative phenomenological analysis (IPA) method helps researchers interpret the differences in the meaning of marriage from two groups of women related to several aspects to produce conclusions; 1) both generations position marriage as a sacred institution, although the Younger Generation emphasizes optional and contextual values, 2) there is a view from the Older Generation that marriage completes happiness, although in the majority non-material welfare is seen as being under the control of the individual, 3) both generations agree that marriage has the potential to present an economic burden, although the Older Generation considers marriage to be still relevant in creating financial stability, 4) a happy marriage can only be achieved if there is no domination by one party, either husband or wife, 5) the presence of children is not seen as something natural by the majority of informants, although there is an opinion from the Older Generation that children must be present in marriage, 6) the perception of the Younger Generation is formed from the accumulation of information about their offline and online activities, while the previous generation only relied on physical interaction.